On the Therapeutic Potential of Heme Oxygenase-1 and Its Metabolites - David E. Stec (MDPI AG, 2024)
Over the past 55 years, the heme oxygenase (HO) system has emerged as a pivotal player in a myriad of cellular, tissue, and integrative physiological processes [...]